If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1cotgx = 0 Solving 1 + -1cgotx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1cgotx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1cgotx = 0 + -1 -1cgotx = 0 + -1 Combine like terms: 0 + -1 = -1 -1cgotx = -1 Divide each side by '-1gotx'. c = g-1o-1t-1x-1 Simplifying c = g-1o-1t-1x-1
| 9x+y+1=0 | | 3(3y-xi)-2(2x-3yi)=(5-10I)-(2x-3yi) | | G(x)=-3f(x) | | 1-3y=5 | | 20-12=4(x-5) | | 5x+8y=-16 | | 16x+200=100 | | 4(u-4)-7=-3(-5u+3)-u | | 0=x^2-8x-209 | | 16x^2+x-7=0 | | X(6x+5)=0 | | 20=9x+2-3x | | Y=16t^2+80t+224 | | 2w+4w-3w= | | a(bx+4)=cx-8 | | 5+2x(3x-4)+6=2x(5x-2) | | -2y+8=-3 | | -(2x-1)(x-5)=0 | | 4*cos(7x)=0 | | 4m-3g+4m-8g= | | (-2x+1)(3x+4)=0 | | 2(5-8(.25))-5=-5(2(.25)+1) | | 4.29t^2-4.29t+0.65=0 | | 2(5-8(1.66))-5=-5(2(1.66)+1) | | 7x-4-(4x-2)=-(x+5)-6x+4 | | 4.29x^2-4.29t+0.65=0 | | 2(5-8(1.6))-5=-5(2(1.6)+1) | | -3(t+2)=9 | | (6x+7)=-3 | | 8x^2-64x-48=0 | | 4x-2x+4=6 | | 13+6t-2t+1= |